PENYELESAIAN SENGKETA KETERLAMBATAN PENYELESAIAN PEKERJAAN DALAM PELAKSANAAN KONTRAK KERJA KONSTRUKSI DI PT. TRI JAYA NASIONAL - Wira Permata Sari, A. A.; Wiryawan, I Wayan; Wiratni Darmadi, A. A. Sagung (Kertha Semaya : Journal Ilmu Hukum, 2013)
This research was entitled “Dispute Resolution Of Delay In Completion Work Construction of Contract” meanwhile the background of this research issue was that the rapid economic growth in Indonesia followed by the rapid development of infrastructure, so that the rapid construction activities in the communities in the implementation are usually made in writing or commonly called the construction contract. However, it is not uncommon in the implementation disputes arise between the parties one of which is the delay completion of the work by the contractor. Based on this background, the authors raised the formulation of the problem include: how the dispute settlement mechanism of the delay completion of the work in the implementation of construction work contacts. Legal research is empirical legal research study. Namely conceptualizing an empirical phenomenon that can be observed in real life. while to collect data from the field study used interviews and documents. Based on the discussion of this study, obtained results that the first dispute resolution adopted by the PT.TRI JAYA NATIONAL is the path that is non-litigation negotiations. However, if the non-litigation path then the path will be taken by non-litigation.
Keywords: Dispute Resolution, Construction Of Contracts, And Delay Completion Of The Work